Effect of Silodosin, an Alpha1A-Adrenoceptor Antagonist, on Ventral Prostatic Hyperplasia in the Spontaneously Hypertensive Rat - Shimizu, Shogo (PLoS One, 2015)
BACKGROUND: A decreased prostatic blood flow could be one of the risk factors for benign prostatic hyperplasia/benign prostatic enlargement. The spontaneously hypertensive rat (SHR) shows a chronic prostatic ischemia and hyperplastic morphological abnormalities in the ventral prostate. The effect of silodosin, a selective alpha(1A-)adrenoceptor antagonist, was investigated in the SHR prostate as a prostatic hyperplasia model focusing on prostatic blood flow. METHODS: Twelve-week-old male SHRs were administered perorally with silodosin (100 μg/kg/day) or vehicle once daily for 6 weeks. Wistar Kyoto (WKY) rats were used as normotensive controls and were treated with the vehicle. The effect of silodosin on blood pressure and prostatic blood flow were estimated and then the prostates were removed and weighed. The tissue levels of malondialdehyde (MDA), interleukin-6 (IL-6), chemokine (C-X-C motif) ligand 1/cytokine-induced neutrophil chemoattractant 1 (CXCL1/CINC1), tumor necrosis factor-alpha (TNF-α), transforming growth factor beta 1 (TGF-β1), basic fibroblast growth factor (bFGF) and alpha-smooth muscle actin (α-SMA) were measured. The histological evaluation was also performed by hematoxylin and eosin staining. RESULTS: There was a significant increase in blood pressure, prostate weight, prostate body weight ratio (PBR), tissue levels of MDA, IL-6, CXCL1/CINC1, TNF-α, TGF-β1, bFGF and α-SMA in the SHR compared to the WKY rat. The ventral prostate in the SHR showed the morphological abnormalities compared to the WKY rat. Prostatic blood flow was decreased in the SHR. However, treatment with silodosin significantly restored the decreased prostatic blood flow in the SHR. Moreover, silodosin normalized tissue levels of MDA, IL-6, CXCL1/CINC1, TNF-α, TGF-β1, bFGF and α-SMA, and it ameliorated ventral prostatic hyperplasia in the SHR excluding blood pressure. Silodosin decreased PBR but not prostate weight in the SHR. CONCLUSIONS: Silodosin can inhibit the progression of prostatic hyperplasia through a recovery of prostatic blood flow.